2007
DOI: 10.1038/ni1518
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clonogenic common Flt3+M-CSFR+ plasmacytoid and conventional dendritic cell progenitors in mouse bone marrow

Abstract: Lymphoid tissue plasmacytoid and conventional dendritic cells (DCs) are continuously regenerated from hematopoietic stem cells. The cytokine dependence and biology of plasmacytoid and conventional DCs suggest that regeneration might proceed through common DC-restricted developmental intermediates. By selecting for cytokine receptor expression relevant to DC development, we identify here highly cycling Lin(-)c-Kit(int)Flt3(+)M-CSFR(+) cells with a distinct gene-expression profile in mouse bone marrow that, on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
627
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 604 publications
(655 citation statements)
references
References 49 publications
19
627
2
7
Order By: Relevance
“…The macrophage and DC precursor (MDP) for lymphoid tissue conventional DCs (cDCs), pDCs and monocytes is characterized as a cell expressing Lin À c-kit hi CD115 1 CX 3 CR1 1 Flt3 1 [8,26]. Another distinct progenitor is called the common DC precursor (CDP) (Lin À c-kit low CD115 1 Flt3 1 ) and is restricted to produce cDCs and pDCs, but not monocytes [27,28]. Preliminary data showed that ER-MP58 1 cells do not express Flt3 and do not produce pDCs when cultured in the presence of Flt3 in the fetal and pre-diabetic pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…The macrophage and DC precursor (MDP) for lymphoid tissue conventional DCs (cDCs), pDCs and monocytes is characterized as a cell expressing Lin À c-kit hi CD115 1 CX 3 CR1 1 Flt3 1 [8,26]. Another distinct progenitor is called the common DC precursor (CDP) (Lin À c-kit low CD115 1 Flt3 1 ) and is restricted to produce cDCs and pDCs, but not monocytes [27,28]. Preliminary data showed that ER-MP58 1 cells do not express Flt3 and do not produce pDCs when cultured in the presence of Flt3 in the fetal and pre-diabetic pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, these cells were termed monocyte-derived DCs (Mo-DCs) to discriminate them from classical and plasmacytoid DCs which are derived from a separate progenitor [48][49][50][51]. These Mo-DCs were characterized in particular under inflammatory conditions and include Tip-DCs (TNF-α-and iNOS-producing DCs), DC-SIGN + DCs and CX3CR1 + lamina propia DCs of the small intestine [23,48,52,53] (Fig.…”
Section: Development and Functions Of Macrophagesmentioning
confidence: 99%
“…In mice it has been shown that conventional DC (cDC) and pDC can develop from minor Flt3 1 subpopulations within the common myeloid and the common lymphoid progenitor pools [5][6][7]. Recently, this pool was narrowed down to a DC committed precursor (pro-DC) that can only develop into cells of the DC lineages [8,9]. It is not clear yet at what point in DC development the commitment to a subpopulation is accomplished.…”
mentioning
confidence: 99%